Comments on Higham and Heep (2017): 'Reply to: "In the eye of the beholder: contextual issues for Bayesian modelling at the middle-to-upper Palaeolithic transition", by Discamps, Gravina and Teyssandier (2015)'. Issue 1 (1st January 2019) - Discamps, Emmanuel; Gravina, Brad; Teyssandier, Nicolas
ABSTRACT: In a response to our initial demonstration of the extreme sensitivity of Bayesian models for the Western European Middle-to-Upper Palaeolithic transition, Higham and Heep attempt to refute some of our arguments. They maintain that our modifications to their individual site models bear no meaningful impact and hence Higham et al.'s overall conclusion of a Mousterian-Châtelperronian coexistence in France remains valid. Such a scenario would considerably alter current perceptions of late Neanderthal cultural dynamics and potential interactions with modern human groups across Western Europe. Given the role of the Châtelperronian in on-going discussions concerning the final Neanderthals, establishing a reliable chronological framework for this techno-complex is fundamental. In addition to the high susceptibility of Bayesian models to even minor modifications, we maintain that secure, taphonomically tested contexts are the necessary prerequisite for model construction. We would like to take this opportunity to quickly address several of their context-specific criticisms and their general misinterpretation of the overall aim of our original critique.